Pengaruh Core Stability Dan William Exercise Terhadap Penurunan Nyeri Punggung Bawah Pada Kuli Panggul Beras Di Daerah Jati Kurung Kabupaten Karanganyar - Herawati, Desita; , Totok Budi Santoso, SST,FT, M.P.H (2017)
This research aims to know the influence of core stability and william exercise against a decrease lower back pain in the pelvic area of rice on labour Teak Brackets Karanganyar Regency. The research method used is the type of experimental research with approach of a quasi experimental design research pre test and post test with control group design. The sample used in this study as many as 20 respondents with a grouping of 10 respondents group control and 10 respondents group experiments. To practice Core Stability is given for 3 times a week is funded for 4 weeks, with 10 counts with 3 times the repetition exercise Exercise exercise dose William 3 times a week for 4 weeks. Technique of data analysis used in this study by Univariate analysis menggunkanan and Bivariat analysis menggunkanan with the Wilcoxon. The results showed there is the influence of core stability exercise therapy against a decrease in pain, improved balance and functional capabilities of the patient's lower back pain which shows sig (0.004) < 0.05. There is Pengarug which means administering the treatment william exercise against a decrease lower back pain in the pelvic area in rice kuli Teak Brackets Karanganyar Regency which shows sig (0.007) < 0.05. Keywords: Core Stability, William Exercise, Back Pain